EDUCATIONAL THOUGHTS OF DEWI SARTIKA (Study of Analysis of Islamic Education Values) - syahwan Tumanggor; Nurul Asyikin; Amriansyah Pohan (Sufiya Journal of Islamic Studies, 2023)
National History has recorded at least some big names behind the Indonesian educational mindset, one of which is Dewi Sartika. Dewi Sartika is a figure who fights for women's education. A distinctive pattern in the thought and practice of Dewi Sartika's education is the integration of general science with religious values. This type of article research is library research. The article is prepared with a descriptive-critical method with more emphasis on the power of analysis of existing sources and data. The results showed that the thought and practice of Dewi Sartika's education contained so many Islamic values. This can be seen from the thoughts, vision and mission, ideals, goals, and educational practices that have been carried out by Dewi Sartika.